Decadal in situ hydrological observations and empirical modeling of pressure head in a high-alpine, fractured calcareous rock slope - R. Scandroglio; S. Weber; S. Weber; T. Rehm; M. Krautblatter (Earth Surface Dynamics)
In peri- and paraglacial regions, water plays a critical role in the hydrological cycle and slope stability. However, hydrological models often overlook water infiltration into bedrock due to limited knowledge of groundwater dynamics at high elevations. Although the link between water presence and rock slope failures is evident in many cases, proof of hydrostatic pressure buildup at depth is scarce, highlighting another significant research gap. This study aims to decipher the hydrological dynamics and empirically derive hydrostatic pressures in deep bedrock. We present unique decennial meteorological data, snowmelt modeling, and discharge measurements from two rock fractures in a tunnel located at ≈ 55 m depth under the permafrost-affected Zugspitze ridge (2815–2962 m a.s.l.). We developed an empirical hydraulic model and detected flow anomalies by comparing inputs (i.e., snowmelt and rainfall) and outputs (i.e., discharge from fractures, baseflow, and no-flow events). Results show continuous flow during snowmelt and discontinuous events during summer months. Hydraulic conductivities are in the order of 10−4 m s−1, with variations according to the saturation. Extreme events are likely to fully saturate the fractures and increase their interconnectivity, producing discharges up to 800 L d−1 and 58 L h−1 from one single fracture. Hydrostatic pressures calculated implementing Darcy's falling-head law are 27 ± 6 m during average snowmelt and 40 ± 10 m for extreme events. These pressure levels can weaken or even destabilize rock slopes in rapidly warming alpine environments. With ongoing climate changes, water relevance is expected to increase, with impacts that have yet to be fully assessed. This study advances the understanding of alpine hydrology and geomorphology by providing new insights into deep groundwater processes and their implications for slope stability.